Die rekenmeestersprofessie en eksternaliteite - ’n oorsig - Lubbe, D. S. (Koers, 1993)
Since the first textbook on accounting was written approximately five centuries ago, the theory of accounting has changed and developed fundamentally. However, one field that has remained almost unchanged throughout the centuries is the accounting approach to externalities. The largescale interest in environmental issues has again placed the accounting approach to externalities under scrutiny. In this article an oven'iew is given of the development of the concept of externalities. The possible future influence of externalities on accounting and the accounting profession are also focused on.